The ChCl/HGA-based DES as a capable and new catalyst for the green synthesis of benzo[4,5]thiazolo[3,2-a]chromeno[4,3-d]pyrimidin-6-one - Elnaz Chegeni; Davood Habibi; Arezo Monem; Zahra Jahaniyan (Scientific Reports)
Abstract A novel deep eutectic solvent (ChCl/HGA-DES) was prepared by a mixture of two moles of choline chloride (ChCl) and one mole of 2,3-dihydroxybenzoic acid (hypogallic acid, HGA). The eutectic point phase diagram showed that the two moles of ChCl and one mole of HGA is the best molar ratio for synthesizing a novel DES. Then, ChCl/HGA-DES was characterized by the FT-IR, TGA/DTA, densitometer, eutectic points, and 1HNMR techniques and used as a novel and capable catalyst for the green synthesis of six new benzo[4,5]thiazolo[3,2-a]- chromeno[4,3-d]pyrimidin-6-ones 5(a-f) and five new (2-(2-hydroxyphenyl)-8-methyl-4-phenyl-4H-benzo[4,5]thiazolo[3,2-a]pyrimidin-3-yl)(morpholino)methanones 6(a-e) through one-pot condensation reactions.